Peranan Konseling Pastoral dalam Gereja bagi Pemulihan Kesehatan Rohani Jemaat - Samuel Irwan Santoso (Sekolah Tinggi Teologi Erikson-Tritt Manokwari, 2021)
This study specifically outlines the role of pastoral counseling in the church for the restoration of the spiritual health of the church. This paper uses qualitative methods with a literature study approach. The description in this article describes that the interpersonal relationships between counselors and their consensual. Counseling comes from the Latin